(untitled) (Journal of Forestry, 2024)
Black pine is the third most widespread tree species (4.2 million ha) in Türkiye and due to its important position in Turkish forestry, it has been studied in many ways. In this study, the influence of the main climatic variables with soil wetness in the root zone on the radial growth of black pine was investigated. Tree ring widths were measured with Cdendro and CooRecorder, and standard dendrochronological techniques were used for cross-dating, standardization, and statistical analysis based on the xDateR and dplR packages in R. According to the result of this study, spring and summer precipitation mostly plays a significant positive role for the radial growth of black pines in Arıt in the western Black Sea region. Although maximum temperature has no influence, minimum and average temperatures in November and December of the previous year affect the radial growth significantly and negatively. In addition, soil moisture of the root zone in June and August has a clearly positive effect on radial growth.